2019
DOI: 10.7554/elife.42951
|View full text |Cite
|
Sign up to set email alerts
|

Regulator of G protein signaling 12 enhances osteoclastogenesis by suppressing Nrf2-dependent antioxidant proteins to promote the generation of reactive oxygen species

Abstract: Regulators of G-protein Signaling are a conserved family of proteins required in various biological processes including cell differentiation. We previously demonstrated that Rgs12 is essential for osteoclast differentiation and its deletion in vivo protected mice against pathological bone loss. To characterize its mechanism in osteoclastogenesis, we selectively deleted Rgs12 in C57BL/6J mice targeting osteoclast precursors using LyzM-driven Cre mice or overexpressed Rgs12 in RAW264.7 cells. Rgs12 deletion in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 59 publications
0
41
0
Order By: Relevance
“…Red O staining or osteogenic medium (αMEM with 10% FBS, 10 nM dexamethasone, 10 mM βglycerophosphate, 50 µg/mL ascorbic acid, 100 IU/mL penicillin, and 100 μg/mL streptomycin) For in vitro osteoclastogenesis, bone marrow cells flushed from long bones were seeded to dishes for obtaining bone marrow macrophages (BMMs) as described previously (64,65).…”
Section: Cell Culturementioning
confidence: 99%
“…Red O staining or osteogenic medium (αMEM with 10% FBS, 10 nM dexamethasone, 10 mM βglycerophosphate, 50 µg/mL ascorbic acid, 100 IU/mL penicillin, and 100 μg/mL streptomycin) For in vitro osteoclastogenesis, bone marrow cells flushed from long bones were seeded to dishes for obtaining bone marrow macrophages (BMMs) as described previously (64,65).…”
Section: Cell Culturementioning
confidence: 99%
“…RGS12 is expressed in chondrocyte mitochondria, cytoplasm, and nucleus RGS12 has been identified as a protein related to cell proliferation, differentiation, oxidative phosphorylation, ROS production, and apoptosis 19,25 . These observations indicate that RGS12 may play a key role in mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to a central RGS domain, RGS12 contains a PDZ (PSD-95/discslarge/ZO-1 homology) domain, a PTB (phosphotyrosine-binding) domain, a tandem repeat of Ras-binding domain and a GoLoco domain 24 . Our previous studies found that RGS12 is highly expressed in bone cells and regulates the function of osteoblasts and osteoclasts 19,25 . Endochondral bone growth is critically driven by the transformation of cartilage into bone tissue as a result of cell proliferation, differentiation, and apoptosis within the growth plate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, OC formation and activity (resorption areas) were also potently suppressed with febuxostat at 60 µM ( Figure 1F). Because ROS has been recognized as an intracellular signal mediator for RANKL-induced OC differentiation [11,21,22], these results suggest that febuxostat can act as an inhibitor for RANKL-induced osteoclastogenesis through the suppression of ROS production.…”
Section: Febuxostat Inhibits Rankl-induced Ros Production and Oc Formmentioning
confidence: 85%